Synergistic Effect for LiMn2O4 Microcubes with Enhanced Rate Capability and Excellent Cycle Stability for Lithium Ion Batteries. Issue 2 (1st January 2016) - Lu, Jia; Fan, Xiaoyong; Zhou, Cuifeng; Liu, Zongwen; Zheng, Feng; Lee, Kim Seng; Lu, Li
Abstract : Monodispersed porous LiMn2 O4 microcubes assembled with closely-packed nanograins and coated with Mn2 O3 have been prepared through a solid state reaction between LiOH and MnO2 microcubes, the latter obtained via hydrothermal treatment. Scanning electron microscopy and transmission electron microscopy are utilized for microstructure investigation and nanograins, macropores and Mn2 O3 surface overlayer are clearly observed. Cyclic voltammography and galvanostatic charge-discharge technique are employed to study the electrochemical performance of LiMn2 O4 . The results show that the LiMn2 O4 microcubes have superior high rate capability, delivering an initial discharge capacity of 120 mAh g −1 at 0.1 C and 94 mAh g −1 even at a high rate of 20 C. Moreover, the cycling performance of the cathode is also outstanding. 80% of initial discharge capacity can be preserved when cycled at 10 C for 500 cycles. The improved performance suggests that the prepared LiMn2 O4 microcubes are highly promising for high power lithium batteries.